Pengaruh Visual Merchandising, Online Customer Review, Dan Online Customer Rating Terhadap Keputusan Pembelian Produk EIGER Di Marketplace Shopee (Studi Pada Konsumen Produk EIGER di Kota Malang) - Fatimatus Zahro; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2026)
Abstract This study examines the impact of Visual Merchandising, Online Customer Reviews, and Online Customer Ratings on purchase decisions for Eiger products at the official Shopee store in Malang City. Adopting a quantitative methodology, it targets consumers in Malang who have bought Eiger items via Shopee, with a sample of 150 respondents chosen through purposive sampling. Primary data from questionnaires were analyzed using SPSS version 26.0. Findings reveal that these three factors collectively exert a positive and significant effect on buying decisions, with each element individually demonstrating substantial influence as well. The results highlight the critical role of online store visuals, customer feedback, and star ratings in shaping consumer choices for Eiger purchases on Shopee. Keywords: Visual Merchandising, Online Customer Review, Online Customer Rating, Purchasing Decisions